PERENCANAAN RUTE JARINGAN LINTAS ANGKUTAN BARANG DI KOTA PEKANBARU DENGAN APLIKASI PTV VISUM: PERENCANAAN RUTE JARINGAN LINTAS ANGKUTAN BARANG DI KOTA PEKANBARU DENGAN APLIKASI PTV VISUM - Rahmat Tisnawan; Fitra Ramdhani; Muhammad Rifky Ariansyah (LPPM Universitas Abdurrab, 2021)
The increase in freight movement in Pekanbaru is not followed by the development of good freight transport facility, causing traffic creasing caused by mixtraffic, thus degrading the performance of road segments in Pekanbaru City. It demands the need for the preparation of more effective and efficient freight transport facilities. In an effort to improve the performance of the road segment, several handling scenarios are implemented by cross network arrangement and capacity building of road segments crossed by freight transport. To know the performance of the road segment, the burden of each handling scenario, including in plan year 2030. Based on the result of the loading analysis, it is found that the scenario of ring road construction and road network of freight transport shows the improvement of road performance, where the speed in the base year 33.43 km / hour increases to 40.02 km / h in 2025 and becomes 39.41 km / hr.